METAPHYSICS OF FEAR IN ART - L. G. OREKHOVA (Вестник Донского государственного технического университета, 2018)
Various aspects of an artistic image of fear and types of fear in art are considered in this article. Art promotes formation of the various attitude to fear in a society. In helps to comprehend his value, and also to produce technologies of his overcoming.